ENGINEERING REPRODUCIBLE DATA FOUNDATIONS FOR TRUSTWORTHY ENTERPRISE ANALYTICS: A VERSION-AWARE FRAMEWORK FOR ANALYTICAL STATE RECONSTRUCTION, VALIDATION, AND AUTONOMOUS RECOVERY - Chalapathi Koneni ,Venkata Ratna Kumar Bonagiri (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Reproduction of enterprise analytics is problematicdue to the constantly changing data sources, logic of transformation, semantic definitions and executionenvironments. In this study, an analytical frameworkbased on version awareness is suggested, whichrepresents analytical states by an identity of thesources, versions of a particular transformation,dataset releases